1985
DOI: 10.1017/s0033822200007104
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Atmospheric 14C Variations on the 14C Levels in the Jordan River System

Abstract: ABSTRACT. '3C and 14C were measured in the upper Jordan River, in its tributaries which issue from the Mount Hermon aquifer, and in the local atmospheric CO2 to evaluate the degree to which changes in the atmospheric 14C levels influence the 14C levels in the aquifer and in the Jordan River. The exchange fraction of CO2 between the river and the atmosphere was calculated for fall 1983 with the two carbon isotopes and it is shown that the value obtained with 14C (0.364) is the more reliable. The ratio of 14C i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
14
0

Year Published

1987
1987
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 12 publications
(17 reference statements)
4
14
0
Order By: Relevance
“…Hence, the correlation between the ␦ 13 C atm and the sedimentary ␦ 13 C car implies that the Jordan River waters and its allochthonous carbonate (from which about 40% is due to authigenic precipitation within the Jordan River; Stiller et al 1988) are sensitive to changes in ␦ 13 C atm . A similar conclusion was reached by Carmi et al (1985) based on 14 C measurements and is supported by (only) three ␦ 13 C DIC measurements in the Jordan River showing a change from Ϫ6.3‰ to Ϫ7.4‰ and then Ϫ9.8‰ from 1972 to 1983 and 1998, respectively (Stiller et al 2001). Nevertheless, considering various anthropogenic activities in the lake's watershed that might also affect the ␦ 13 C DIC of the Jordan River (such as drainage from fish ponds and irrigated land crops), ␦ 13 C atm changes over the past few decades probably were not the sole driving force for these observed trends.…”
supporting
confidence: 62%
“…Hence, the correlation between the ␦ 13 C atm and the sedimentary ␦ 13 C car implies that the Jordan River waters and its allochthonous carbonate (from which about 40% is due to authigenic precipitation within the Jordan River; Stiller et al 1988) are sensitive to changes in ␦ 13 C atm . A similar conclusion was reached by Carmi et al (1985) based on 14 C measurements and is supported by (only) three ␦ 13 C DIC measurements in the Jordan River showing a change from Ϫ6.3‰ to Ϫ7.4‰ and then Ϫ9.8‰ from 1972 to 1983 and 1998, respectively (Stiller et al 2001). Nevertheless, considering various anthropogenic activities in the lake's watershed that might also affect the ␦ 13 C DIC of the Jordan River (such as drainage from fish ponds and irrigated land crops), ␦ 13 C atm changes over the past few decades probably were not the sole driving force for these observed trends.…”
supporting
confidence: 62%
“…The validity of 14 C ages depends on correct assessment of equilibrium between the precipitating CaCO 3 and atmospheric CO 2 . Schramm et al (2000) estimated a reservoir age of 1.0 ka, based on 14 C data on organic material and aragonite, and measurements of Dead Sea water (Carmi et al, 1985) collected before the 1978 overturn. Our updated evaluation indicates a best fit with the coral data if the reservoir correction is 1.2 ka.…”
Section: U-th and 14 C Agesmentioning
confidence: 99%
“…A 14 C DIC between Dan source and Arik bridge is 23 pMC according to Carmi et al [1985], and 13 pMC in this study; see Table 1 value, as compared to the 14 C content of its tributaries (water sources). Ε is defined by the equation (Carmi etal.…”
Section: Dissolution Reactions and Carbon Isotopes In The Perennial Smentioning
confidence: 52%
“…Moreover, previous studies have shown that the RA varies considerably between the water sources of the lakes (e.g. Carmi et al 1985;Talma et al 1997).…”
Section: Introductionmentioning
confidence: 95%